2017
DOI: 10.1164/rccm.201612-2497oc
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Polysomnography Is Not Necessary for the Management of Most Patients with Suspected Obstructive Sleep Apnea. Noninferiority, Randomized Controlled Trial

Abstract: Home respiratory polygraphy management is similarly effective to polysomnography, with a substantially lower cost. Therefore, polysomnography is not necessary for most patients with suspected sleep apnea. This finding could change established clinical practice, with a clear economic benefit. Clinical trial registered with www.clinicaltrials.gov (NCT 01752556).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
84
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(97 citation statements)
references
References 33 publications
3
84
0
10
Order By: Relevance
“…There is a strong contradiction between this statement and the continuous efforts of payers favouring the replacement of polysomnography by home sleep testing mainly using respiratory polygraphy. The largest study to date in the field19 suggests that in patients referred with intermediate-to-high suspicion of sleep apnoea, home respiratory polygraphy management is non-inferior to polysomnography, with a substantially lower cost. Midterm outcomes were the same for the Epworth Sleepiness Scale at 6 months, quality-of-life measures, blood pressure or CPAP adherence.…”
mentioning
confidence: 99%
“…There is a strong contradiction between this statement and the continuous efforts of payers favouring the replacement of polysomnography by home sleep testing mainly using respiratory polygraphy. The largest study to date in the field19 suggests that in patients referred with intermediate-to-high suspicion of sleep apnoea, home respiratory polygraphy management is non-inferior to polysomnography, with a substantially lower cost. Midterm outcomes were the same for the Epworth Sleepiness Scale at 6 months, quality-of-life measures, blood pressure or CPAP adherence.…”
mentioning
confidence: 99%
“…This could lead to underestimation of the AHI in RP in relation to PSG and may generate misdiagnosis in patients diagnosed with RP. Nevertheless, a recent randomised controlled trial34 compared the long-term effectiveness of RP and PSG management protocols in a large population of patients with intermediate-to-high suspicion of OSA who were treated with or without CPAP. That study found that the effectiveness of the RP protocol (assessed by ESS) was not inferior to that of the PSG protocol.…”
Section: Discussionmentioning
confidence: 99%
“…That notwithstanding, a recent prospective multicenter study has shown that HSAT is comparable to polysomnography, with the additional benefit of a substantially lower cost [30]. Furthermore, the HSAT portable monitor we used for this study is potentially superior to other similar devices such as the ApneaLink TM (ResMed Corporation, Poway, CA, USA), which was used in the SASCA study (NCT02270853) and is being used in the ongoing study NEOSAS (NCT02648087; www.clinicaltrials.gov) because in addition to the nasal cannula, it includes a Pulse Oximeter, and thoracic and abdominal bands capable of measuring respiratory movements and a microphone, all of which increase the device's sensibility for apneas, hypopneas, and oxygen desaturation.…”
Section: Discussionmentioning
confidence: 99%